2017
DOI: 10.1007/s00125-017-4352-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metformin on gut microbiota and the immune system as research frontiers

Abstract: Recent studies have revealed that metformin influences gut microbiota and the immune system although neither is a classic target of the drug. This research has revealed complexity not previously appreciated, and opened new research directions. The extent to which immunomodulatory effects and actions on the microbiota are related to each other and account for effects on host energy metabolism remains to be determined. These sites of action may be relevant not only to the efficacy of metformin for its establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 56 publications
(82 reference statements)
1
67
0
2
Order By: Relevance
“…Accordingly, the gut microbiome appears to be an important, if currently incompletely understood, site of action of metformin. This action of metformin may be relevant not only to its antihyperglycaemia effects but also to other pathologies including disorders of the immune system and cancer …”
Section: Antihyperglycaemic Mechanismsmentioning
confidence: 99%
“…Accordingly, the gut microbiome appears to be an important, if currently incompletely understood, site of action of metformin. This action of metformin may be relevant not only to its antihyperglycaemia effects but also to other pathologies including disorders of the immune system and cancer …”
Section: Antihyperglycaemic Mechanismsmentioning
confidence: 99%
“…108 Similarly, DeFronzo et al showed that delayed-release metformin and immediate-release metformin had comparable effects on glycaemic control, despite the former having only~28% of the bioavailability of the latter. 109 On the basis of these studies, it may be inferred that the gut is an important site of metformin's action.…”
Section: Links To Microbiotamentioning
confidence: 99%
“…In his review, Michael Pollak [30] also discusses the nonglycaemic effects of metformin. He suggests that metformin's function may be partly explained by its effect on the human microbiota (e.g.…”
mentioning
confidence: 99%